Methodology of Individual Accommodation Facilities Research and Estimate of Non-Organized Tourists - VOLKOVA, Tatiana A.; MINENKOVA, Vera V.; FILOBOK, Anatoly A.; MAXIMOV, Dmitry V.; BELIKOV, Mikhail Y. (Journal of Environmental Management and Tourism; Vol 7 No 4 (2016): JEMT Volume VII Issue 4(16) winter 2016DO - 10.14505//jemt.v7.4(16).13, 2017)
Accommodation as an integral part of each tour occupies a central place in the complex of services, which are offered to tourists during the trip. The question of the importance of individual accommodation facilities, their impact on the integrity of the structure of the tourism industry of the country and regions is particularly important. The research was conducted by means of interview of IAF managers and private households (PH) owners. Almost all the interviewees pointed out that the households’ owners often "hide" tourists, introducing them as relatives in order such information not to reach the Tax Service. The hotel industry needs an improvement of the material and technical facilities and further governmental help for the tourism development as well as the aligning of the seasonal misbalance of the resorts and touristic organizations occupation.